2018
DOI: 10.1002/hed.24856
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiotherapy for T1/2N0M0 mucoepidermoid carcinoma positive for CRTC1/3‐MAML2 fusions

Abstract: Background The National Comprehensive Cancer Network (NCCN) guidelines recommend considering postoperative radiotherapy (PORT) for completely resected T1/2N0M0 salivary mucoepidermoid carcinomas when they show tumor spillage, perineural invasion, or intermediate/high‐grade histology. CRTC1/3‐MAML2 fusions have been associated with a favorable clinical outcome. Methods Forty‐seven T1/2N0M0 mucoepidermoid carcinoma cases positive for CRTC1/3‐MAML2 fusions were completely resected and were not treated with PORT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
8
0
4
Order By: Relevance
“…In addition, younger patients may be more likely to be treated less intensively. We recently showed that fusion‐positive MEC patients have an excellent prognosis without postoperative radiation therapy 42 . Whether it is necessary to submit MEC patients to postoperative radiotherapy should be critically considered, especially in the case of young individuals, as the therapy usually has several serious adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, younger patients may be more likely to be treated less intensively. We recently showed that fusion‐positive MEC patients have an excellent prognosis without postoperative radiation therapy 42 . Whether it is necessary to submit MEC patients to postoperative radiotherapy should be critically considered, especially in the case of young individuals, as the therapy usually has several serious adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of CRTC1/3-MAML2 fusion in MEC has been analyzed. Okumura et al (34) reported that in early-stage MEC patients positive for CRTC1/3-MAML2 fusions, an excellent prognosis may be achieved without adjuvant radiotherapy when the tumors are completely resected without tumor spillage. However, Birkeland et al (35) found a high rate of CRTC1/3-MAML2 gene fusions in a large cohort of MEC patients, but the authors did not note any correlation between fusion status and tumor grade or survival.…”
Section: Discussionmentioning
confidence: 99%
“…Aus der t(11;19)(q21;p13)-Translokation resultiert eine CRTC1-MAML2-Transfusion, welche spezifisch für Mukoepidermoidkarzinome ist und in ca. 38-82 % aller Mukoepidermoidkarzinome nachzuweisen ist [11,12]. CRTC1 (auch MECT1, TORC1, WAMTP1) ist ein Koaktivator eines cAMP-response-binding elements (CREB), welcher eine Rolle in der Zelldifferenzierung und -proliferation spielt.…”
Section: Molekulargenetische Grundlagenunclassified
“…Interessanterweise konnte die p53-Mutation aber häufiger bei Fusionsprotein-negativen Mukoepidermoidkarzinomen festgestellt werden, hauptsächlich bei Intermediate-und High-grade-Mukoepidermoidkarzinomen. Bei Vorliegen einer p53-Mutation konnten auch insgesamt mehr Mutationen detektiert werden als bei Mukoepidermoidkarzinomen ohne p53-Mutation [12,17]. Diese Beobachtungen legen die Vermutung nahe, dass die p53-Mutation mit einem genetischen Switch in Verbindung zu bringen ist, durch welche ein Low-grade-in ein High-grade-Karzinom übergeht oder aber auch, dass p53 als eigenständiger Tumor- induktor bei Translokations-negativen Mukoepidermoidkarzinomen wirken könnte.…”
Section: Molekulargenetische Grundlagenunclassified
See 1 more Smart Citation